Territorial capital in regional development - Przygodzki, Zbigniew (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
European Union is seeking a way to enhance development through territorialisation of its policies. In particular in the last decade, the thesis has been confirmed by evolutions observed in regional, innovation and industrial policies. Other body of evidence can be found, inter alia, in the consensus over the leading development directions and the implementation of concepts, such as, e.g.: Place based policy, Smart specialization, Regional Innovation System or Clusters. EU economies are strongly correlated with their respective social backgrounds. Development potential has always been strongly dependent upon categories, like: social capital, trust and norms, formal and informal institutions, culture, and tradition. Hence, following a variety of attempts to find a solution that would foster competitiveness and innovation in the European Union, nowadays we witness looking for growth factors at the local level combined with simultaneous discovery of regional potential in the global space. According to the approach, under the conditions of globalized knowledge-based economy looking from the macroeconomic perspective of aggregated indices we can hardly notice the uniqueness and exceptionality that highlight rare, but at the same time competitive, development factors. Only the change of the level of observation, almost like descending prior to landing, helps us see differences and, first of all, appreciate how appealing the environment is (its investment, location, and institutional attractiveness). It does not mean, however, that until now the regions were “hidden” since they rather did not want, were not able to, did not see the reason for and, finally, did not have appropriate conditions to reveal their market potential and demonstrate their resources. Against this backdrop, the objective of the paper is to explore why the potential of local communities (territories) may be relevant globally and what are its effects for the macroeconomic policy. In particular, we wish to explain the essence and importance of territorial capital in development and identify conditions for the policy based on it.